Reaver (2019), volume 2 ebook The grim after. - Jordan, Justin (Reaver (2019), 2020)
The continent of Madaras once promised a new start for settlers, but 200 years after its discovery, the war rages on. Deep within this savage and untamed land, a darkness builds at that must be stopped at all costs. To do so, the Imperials assemble six of its most despicable prisoners—a turncoat, a skin eater, a sorcerer and his bodyguard, a serial killer, and the Devil's Son—the only ones who can stop the end of the new world. They are Hell's Half-Dozen. Join JUSTIN JORDAN (LUTHER STRODE) and REBEKAH ISAACS (Buffy the Vampire Slayer) for REAVER—a dark, grim fantasy for a post-Game of Thrones world.